Zmiany w konsumpcji i poziomie życia Polaków na tle innych krajów Unii Europejskiej - Mazurek-Łopacińska, Krystyna (Change in Consumption and Level of Life in Poland on Background of Other Countries of the European Union, 2008)
Integration with the European Union sets new challenges for Polish economy and citizens who have lots of expectations concerning membership in the EU. The basis for foreseeing and modeling of adjusting processes released by mechanisms of Europeanization should be recognition and estimation of internal diversity and distance between Polish regions and other European regions. Estimation should be made based on market and consumption activities. This paper shows the changes in level of life in Polish households and satisfaction from living in Poland beside other EU countries. Estimations and analysis were made based upon research reports as well as international statistics. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 44-54